Electrical and Optical Properties of Co(75)Si(15)B(10) Metallic Glass Nanometric Thin Films - Shauyenova, Danagul (Materials (Basel), 2020)
Co-based (Co(75)Si(15)B(10)) thin-film metallic glass (TFMG) with nanometric thicknesses (100~300 nm) was investigated for its structural, electrical, and optical properties. The TFMG structure was examined using scanning electron microscopy and X-ray diffraction, while electrical properties were examined using inductance/capacitance/resistance spectroscopy, cyclic voltammetry, and Hall effect measurements. In addition, optical absorption/reflection/transmittance measurements were performed to examine optical properties. Results revealed that Co-based TFMGs, which have an amorphous structure without surface defects, behave like a dielectric material, with higher resistivity and much lower carrier concentration than pure cobalt (Co) thin films of the same thickness, despite its mobility being modestly larger than its Co counterparts. Meanwhile, the optical investigation of TFMG enabled us to determine the complex relative permittivity (complex relative dielectric constant) [Formula: see text] at a visible wavelength (632.8 nm). Moreover, unlike normal metals, TFMGs exhibited a large positive value of the real part of [Formula: see text] , while exhibiting properties of substantial absorption of light (absorption coefficient α). It was also found that the Co-based TFMG gained optical transparency for thicknesses less than 5 nm. TFMGs demonstrated the nearly thickness-independent properties of the electrical and optical parameters probed, a feature of high-index, dielectric-like material with negligible size effects, which may have applications in micrometer-scaled optoelectronic and magneto-optical devices.